Las Tic En El Proceso De Enseñanza Aprendizaje - Almaguer, Arisdorgan Diéguez; Zaquinaula, Freddy Patricio Ajila; Ramírez, Tatiana María Velázquez; Martínez, Irina Reyes (European Scientific Journal, ESJ, 2017)
The objective of this article is to contribute to the successful incorporation of ICTs in the teaching - learning process as a means of teaching and analysis. At the same time, as seen in this process, they can contribute in making the content of other subjects meaningful and in developing metacognitive strategies in the students. All of these is possible through constructivist foundations and the cultural historical approach of Vygotsky. As a result, the theoretical, empirical, and statistical methods are used according to the research. The main characteristics of the ICT were highlighted, as well as their advantages and disadvantages. Then, methodological treatment on some contents of Mathematics as examples were given. Finally, a didactic model that synthesizes the double role of ICT and that highlights the role of the main actors in the act of teaching and learning was proposed. It, however, addresses the importance of cooperation and multidisciplinary work in achieving the objectives of the study.